Applications of invertebrate animal models to dimorphic fungal infections - Singulani, Junya L. [UNESP]; Scorzoni, Liliana [UNESP]; de Oliveira, Haroldo C. [UNESP]; Marcos, Caroline M. [UNESP]; Assato, Patricia A. [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Mendes-Giannini, Maria José S. [UNESP] (MDPI, 2018)
Dimorphic fungi can be found in the yeast form during infection and as hyphae in the environment and are responsible for a large number of infections worldwide. Invertebrate animals have been shown to be convenient models in the study of fungal infections. These models have the advantages of being low cost, have no ethical issues, and an ease of experimentation, time-efficiency, and the possibility of using a large number of animals per experiment compared to mammalian models. Invertebrate animal models such as Galleria mellonella, Caenorhabditis elegans, and Acanthamoeba castellanii have been used to study dimorphic fungal infections in the context of virulence, innate immune response, and the efficacy and toxicity of antifungal agents. In this review, we first summarize the features of these models. In this aspect, the growth temperature, genome sequence, availability of different strains, and body characteristics should be considered in the model choice. Finally, we discuss the contribution and advances of these models, with respect to dimorphic fungi Paracoccidioides spp., Histoplasma capsulatum, Blastomyces dermatitidis, Sporothrix spp., and Talaromyces marneffei (Penicillium marneffei).
Keywords: Acanthamoeba castellanii; Antifungal; Caenorhabditis elegans; Dimorphic fungi; Galleria mellonella; Host-pathogen interactions; Innate immunity; Virulence